A review of the Best Practice in Radiation Oncology project from 2008 to 2018. (December 2018) - Coffey, Mary; Rosenblatt, Eduardo; Vandevelde, Guy; Osztavics, Andreas; Pasini, Danilo; Scherer, Philipp; Dickie, Colleen; Karadza, Velimir; Van Egten, Viviane; Leech, Michelle
Abstract: The European Society of Radiotherapy and Oncology (ESTRO)/International Atomic Energy Agency (IAEA) Best Practice in Radiation Oncology-a project to train RTT trainers has reached its ten year anniversary and will commence its fifth iteration in 2018. This project commenced as a novel way to address the issue of limited RTT education throughout Europe. In many countries the profession of RTT is not officially recognised and there is no formal education programme. RTT education is frequently a very short component of a broader programme such as diagnostic imaging, nursing or a technical discipline. To date, fifty-nine short courses have been delivered, two RTT-specific National societies have been developed, a South East European cooperation with biannual conferences has evolved and significant progress has been made on improving the radiotherapy-specific content of national educational programmes, which will continue with future iterations of this project.